Visual and interface design mechanisms: Systematic review of ethnomathematics media bridging culture and mathematics - Nadia Shofa Zumara; Eveline Siregar; Iva Sarifah; Imam Fitri Rahmadi (Jurnal Elemen, 2026)
Mathematics education continues to face representational challenges because abstract concepts are often disconnected from students lived and cultural experiences. Although ethnomathematics offers a way to contextualize learning, limited research has examined how visual and interface design may support the links between cultural contexts and formal mathematical understanding. This study presents a systematic literature review of 17 empirical studies from Scopus published between 2020 and 2025, following the PRISMA guidelines. The analysis identified recurring visual and interface design elements used to represent mathematical concepts in culturally meaningful and interactive ways. These elements are associated with three mediational processes: concretization, embodied engagement, and structured cognitive scaffolding, which may support learners in moving from cultural experiences to formal mathematical understanding. The novelty of this review lies in proposing these three constructs as analytical interpretations developed through cross-study thematic synthesis, rather than as mechanisms directly identified or tested within the primary studies. This review offers a design-oriented perspective on ethnomathematics learning and proposes an analytical framework to guide future research and practice, while highlighting the need for further empirical validation across diverse contexts.